From cultural heritage to sustainability: Evaluating green economy in the Gringsing weaving industry using the MULTIMOORA approach - Dewani, I Dewa Ayu Made Natasah; Saskara, Ida Ayu Nyoman (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
The green economy, as a dimension of sustainable development, offers a comprehensive framework for achieving sustainability goals. The Gringsing textile industry in Bali presents a unique opportunity to integrate traditional crafts with principles of a green economy. This study examines the opportunities and challenges of sustainable Gringsing textile production in Tenganan through the lens of green economy principles. The MULTIMOORA (Multi-Objective Optimization by Ratio Analysis plus Full Multiplicative Form) method was employed to evaluate the environmental, economic, and social impacts of production alternatives. The findings reveal that Alternatives A1 and A3 achieved identical aggregate values of 0.84, with distinct strengths. A1 excels in economic viability and social contribution, making it a balanced option for stakeholders seeking comprehensive benefits. In contrast, A3 demonstrates superior environmental performance, making it the preferred choice for initiatives prioritizing ecological sustainability. Opportunities for sustainable Gringsing textile production include market expansion, innovation, and policy support, while challenges encompass high production costs, market competition, and resource constraints.